(untitled) (International Journal of Food and Nutritional Sciences, 2020)
A large proportion of the total labor force in India and most other developing nations is employed in the informal sector. This sector is also known as the ’unorganized sector’. In recent times, the study of this field has become very important not only in economics but also in sociology and psychology. Female laborers make up the majority of India’s unorganized workforce. According to the Council of Applied Economic Research (NCAER), about 97% of female workers are employed in the informal sector. The unorganized industry offers several job opportunities. These include home-based work (e.g., rolling papads and beedis, stitching, traditional painting), self-employment (e.g., selling vegetables), employment in household enterprises, small units, on land as agricultural workers, labor on construction sites, domestic work, and many other forms of casual or temporary employment. In certain families, the male spouse’s earnings are insufficient to maintain the family, or there is no male partner at all. In both cases, the female partner is compelled to become the breadwinner for the family. In such instances, female workers have multiple obligations. They must balance caring for their family with working to support themselves. The education level in backward areas is really poor. Among these, the female education level is significantly lower. Since childhood, they have been required to assist with home chores or compelled to labor, and they have not had the opportunity to attend school. They fail to obtain better occupations. The current study attempts to comprehend the research on the working and living conditions of workers in the informal sector, as well as to identify needs for future research